Sastra Jawa : suatu tinjauan umum - Sedyawati, Edi, 1938- (Jakarta : Pusat Bahasa : Balai Pustaka, 2001)
On Javanese literature; collection of articles
Includes bibliographical references (p. 518-548)
Keywords: Javanese literature -- History and criticism